Synthesis of magnetic multi-walled carbon nanotubes via facile and solvent-free direct doping method for water remediation. (February 2022) - Lee, Cheong Sheng; Shuit, Siew Hoong; Lim, Chuan Chuan; Ng, Qi Hwa; Hoo, Peng Yong; Lim, Steven; Teoh, Yi Peng
Abstract: Background: Owing to the requirement of additional processing steps to separate the spent adsorbents from treated water, magnetic multi-walled carbon nanotubes (MMWCNTs) have recently been hailed as novel adsorbent. Methods: In this study, MWCNTs doped with iron oxide (Fe3 O4 ) nanoparticles (n-MMWCNTs) and MWCNTs doped with polydiallyldimethylammonium chloride (PDDA) coated Fe3 O4 nanoparticles (PDDA-MMWCNTs) were synthesized via solvent-free direct doping method. Prior to the doping process, the pristine MWCNTs were pre-treated with nitric acid. Significant findings: Characterization results such as FTIR, EDX, XRD and zeta potential analysis confirmed the deposition of Fe3 O4 onto the MWCNTs. The stability of the synthesized MMWCNTs under different pH was examined. Detachments of Fe3 O4 from n-MMWCNTs and PDDA-MMWCNTs was found at pH 9 and 3, respectively. Both types of MMWCNTs were applied to the removal of methylene blue (MB). It was found that the MB adsorption capacity of n-MMWCNTs was 11% higher than PDDA-MMWCNTs, due to significantly higher specific surface area of n-MMWCNTs. n-MMWCNTs was found to perform better in alkaline condition in which the adsorption capacity increased about 87% from pH 3 to pH 11. The adsorption of MB on n-MMWCNTs was found to obey the Langmuir isotherm (indicating monolayer MB molecules adsorption on the n-MMWCNTs) with the calculated maximum adsorption capacity of 20.37 mg/g. Moreover, the adsorption of MB followed the pseudo-second order kinetic model. Graphical abstract: Unlabelled Image Highlights: Feasibility of solvent free direct doping method to synthesis magnetic MWCNTs Negligible Fe3 O4 detachment from MWCNTs through solvent free direct doping method. Comparison between MWCNTs doped with uncoated or PDDA coated Fe3 O4 nanoparticles Feasibility of magnetic MWCNTs in the removal of cationic pollutants